Analisis kadar logam Pb, Cd, Cu, As pada air, sedimen dan bivalvia di Pesisir Teluk Balikpapan - Saibun Sitorus; Yerwanto Ilang; Rudy Agung Nugroho (Dinamika Lingkungan Indonesia, 2020)
Analysis of Heavy Metal Content of Pb, Cd, Cu, As in Water, Sediments and Bivalves in Coastal Waters of Balikpapan Bay. The study aims to analyze the levels of heavy metals (Pb, Cd, Cu, As) in water, sediment and Bivalvia and to determine the adsorption, bioconcentration factors in sediments and Bivalvia. This research is in the form of field survey and laboratory analysis, where the results are quantitative descriptive and analyzed statistically multivariate.The results of laboratory analysis showed that the levels of heavy metals in water ranged between (Pb 0.064-0.142 mg/L), (Cd 0.088-0.112 mg/L), (Cu 0.035-0.056 mg/L) and (As 0.022-0.026 mg/L). Sediment (Pb 2,555-2,616 mg/Kg), (Cd 2,433-2,609 mg/Kg), (Cu 1,289-1,553 mg/Kg), (As 0,329-0,496 mg/Kg) and Bivalvia (Pb 1,708-2,076 mg/Kg) ), (Cd 1.569-2.416 mg/Kg), (Cu 1.078-1.264 mg/Kg) and (As 0.297-0.449 mg/Kg). Heavy metal content of Pb, Cd, Cu and As in the sediment is greater than water or Bivalvia. The results of the statistical analysis partially showed that the levels of heavy metals Pb, Cd, Cu and As differed significantly between all study samples (water, sediment and Bivalvia). Whereas the observation stations (Kariangau industrial area, the village on the water and the PT. Pertamina area) did not differ significantly. The results of the analysis of adsorption and bioconcentration factors on the levels of heavy metals Pb, Cd, Cu and As in sediments (Pb 17.99-42.25), (Cd 22.75-28.67), (Cu 26.49-36.83 ) and (As 13.71-19.08). In Bivalvia (Pb 14.15-32.44), (Cd 14.00-26.55), (Cu 21.14-34.43) and As (13.50-29.88).